Polanyi and Schumpeter vs. Neoliberalism: Can Neoliberal World Be Explained by Schumpeter in the Context of Innovation and Polanyi in the Context of the Market? - Akansel, Ilkben (Handbook of Research on Managerial Thinking in Global Business Economics, 2019)
Neoliberalism means “new liberalism.” It could be dated back to 18th century, but it is a term that belongs today. Since 1990, neoliberal rules gave many harmful effects, especially to developing countries, and those harmful effects have proceeded for labor class. As capitalism stands on its own feet, it can find solutions to regain profits. However, the concern may well be gaining too much profit gives harmful effects on a wide range of social classes. Neoliberalism is accepted as the tool of these effects by the majority of the economists. In this chapter, the authors scrutinize the consequences of neoliberalism by the mediation of two great philosophers who criticized capitalism in different ideas. Karl Polanyi's and Joseph A. Schumpeter's different opinions about capitalism will be scrutinized in order to understand the connection between capitalism and neoliberalism. So, in this study, starting with its name, neoliberalism's implementations will be scrutinized by two great philosophers
Keywords: business economics; neoliberalism